The impact of school principal's instructional leadership on enhancing teacher professionalism - Maalip, Fadlan; Amirul Mukminin; Sofyan (Institut Agama Islam Negeri Kendari, 2026)
This study aims to investigate the role of the school principal as an instructional leader in enhancing teacher professionalism at a public senior high school in Merangin Regency, Jambi Province, specifically focusing on the planning, implementation, and impact of this leadership approach, specifically focusing on the planning, implementation, and impact of this leadership approach. The research employs a qualitative descriptive method with a phenomenological approach. Data were collected through participatory observation, semi-structured interviews involving seven participants (the principal, teachers, and administrative head), and document analysis followed by thematic analysis using the Miles and Huberman model supported by ATLAS.ti software. The main findings indicate that the principal effectively functioned as an instructional leader by establishing a clear learning vision, conducting constructive academic supervision, and facilitating continuous professional development, which collectively led to significant improvements in teacher professionalism and teaching practices.